2010
DOI: 10.5194/hess-14-79-2010
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of groundwater discharge to the overall water budget of two typical Boreal lakes in Alberta/Canada estimated from a radon mass balance

Abstract: Abstract. Radon-222, a naturally-occurring radioisotope with a half-life of 3.8 days, was used to estimate groundwater discharge to small lakes in wetland-dominated basins in the vicinity of Fort McMurray, Canada. This region is under significant water development pressure including both oil sands mining and in situ extraction. Field investigations were carried out in March and July 2008 to measure radon-222 distributions in the water column of two lakes as a tracer of groundwater discharge. Radon concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…Changes in both surface water and groundwater affect local and regional recharge and discharge to the wetlands and shallow lakes common in the area . Schmidt et al (2010) showed that a combination of stable isotope and radon mass balance approaches provides information on water flow path partitioning that is useful for evaluating surface-groundwater connectivity (i.e., connectivity of lakes and rivers to underlying aquifers).…”
Section: Oil Sands Examplementioning
confidence: 99%
“…Changes in both surface water and groundwater affect local and regional recharge and discharge to the wetlands and shallow lakes common in the area . Schmidt et al (2010) showed that a combination of stable isotope and radon mass balance approaches provides information on water flow path partitioning that is useful for evaluating surface-groundwater connectivity (i.e., connectivity of lakes and rivers to underlying aquifers).…”
Section: Oil Sands Examplementioning
confidence: 99%
“…Radon ( 222 Rn) is an excellent natural groundwater tracer because of its conservative nature and the high concentrations in groundwater relative to surface water. 222 Rn has been used successfully to trace groundwater inputs in lakes (Schmidt et al 2010), rivers (Cook et al 2006), estuaries (Charette and Buesseler 2004;Santos et al 2012a), coral reefs (Cardenas et al 2010), and the coastal ocean (Burnett et al 2006). The large range of systems where 222 Rn has been used to trace groundwater highlights the utility of this tracer.…”
mentioning
confidence: 99%
“…[48]) or freshwater environments (e.g. [49]), submarine groundwater discharge (e.g. [50][51][52]) or groundwater contamination (e.g.…”
Section: Tracing Applicationsmentioning
confidence: 99%